Mapping and navigating context for opportunity development: The Context Hive – a research-based framework. Issue 4 (August 2021) - Ramsgaard, Michael Breum; Thomassen, Mette Lindahl; Williams-Middleton, Karen; Neergaard, Helle
Contextual elements play an important role in entrepreneurial activities and learning processes. However, context is often taken for granted rather than being viewed as an asset, which may lead to missed opportunities, missed potential solutions and missed learning. Entrepreneurship education should therefore prepare and empower students to act entrepreneurially in their individual, unique context. A student-centric pedagogical approach is required to build this metacognitive understanding and enable students to ultimately self-manage their own process, embedded in and influenced by context. This paper presents a framework, the Context Hive, which enables students to understand and work with the impact of context on their entrepreneurial activity. The Context Hive translates entrepreneurship and context theories into educational (and entrepreneurial) practice by structuring complexity and uncertainty in ways that help students to better grasp, adapt or adjust to contextual elements. Using the research-based framework facilitates dialogue, builds awareness and enables prioritization of actions based on contextual analysis. In this way, the classroom is no longer limited to one perspective and educator and student share responsibility for how learning is designed, which provides a means for educators and students to raise awareness of how context influences entrepreneurial activity, making it navigable.